The Implementation of Total Quality Management in Islamic Junior High Schools: Commitment, Continuous Improvement, and Performance Outcomes - Marisa Juwitasari; Umi Muawanah; Oyong Lisa (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in an Islamic boarding-based bilingual junior high school and to explore its implications for institutional performance and educational quality improvement. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and document analysis involving school leaders, teachers, educational staff, and students. The study examined six core dimensions of TQM implementation: leadership commitment, customer focus, total involvement, continuous improvement, data-driven decision making, and systematic management practices. The findings indicate that TQM principles have been substantially integrated into institutional management and academic processes, contributing positively to performance enhancement, learning quality improvement, and infrastructure development. However, challenges persist in maintaining implementation consistency, strengthening organizational structure, and enhancing staff understanding of comprehensive TQM concepts, particularly among personnel holding multiple roles. The study implies that sustained leadership commitment, capacity building, and structured quality management systems are essential to optimize TQM effectiveness in Islamic educational institutions.